ISLAMIC ETHICS - Abdul Haq Ansari (International Institute of Islamic Thought, 1989)
Islamic ethics as a discipline or a subject does not exist at the present. We do not have works that define its concept, outline its issues, and discuss its problems. What we have, instead, is a discussion by various writers-philosophers, theologians, jurisprudents, sufis and political and economic theorists- in their particular fields of some issues that are either part of, or relevant to, Islamic ethics. Philosophers like Abu Nasr al Farabi (d. 329/950) and Abu 'Ali Miskawayh (d. 421/1030), in their ethical works, have mostly rehashed Greek ethics. True, they have introduced, here and there, some Islamic terms and concepts and modified some notions that hurt their Islamic susceptibilities. But this does not make their ethics Islamic. They do not raise many issues that Islamic ethics must raise, and many ideas they have set forth cannot be considered to be Islamic unless they are seriously modified. Theologians have, indeed, discussed some very important questions of Islamic ethics, such as the source of ethical knowledge. the meaning of ethical terms, and the basis of moral obligation. The views they have expounded are extremely significant. But they have been treated as part of theology rather than ethics, and they form only one aspect of Islanlic ethics. Works on sufism. principles of jurisprudence (usul al fiqh), principles of government and administration (al ahkam al sultaniyah), and public revenue and expenditure (al khara;), also touch upon ideas that are part of, or relevant to, Islamic ethics. We have in them an analysis, for instance, of some ethical virtues, a discussion on motives, priorities and preferences, levels of obligation, and political and economic justice. There is, in short, much material scattered in the works of various disciplines that can be utilized to develop Islamic ethics. At present, while the discipline of Islamic ethics does not exist, it can be developed. Thirty years ago, Islamic economics did not exist, but thanks to the devotion of a number of scholars, we now have Islamic economics. I am sure that Islamic ethjcs will take even less time to develop, provided we give it the required effort. Let us hope this conference of ours initiates the process. In this paper, I will try first to define the task Islamjc ethics should perform, and then review, in that light, various streams of writings to which I have referred, and see what contribution each of these can make to the subject ...